Strategi Pengembangan Koperasi Simpan Pinjam dan Pembiayaan Syariah (KSPPS) Baitul Maal Wa Tamwil (Bmt) Rukun Abadi di Kabupaten Karawang - Sri Hayati (Journal on Education, 2023)
The poverty rate that continues to increase in Karawang Regency makes the Baitul Maal Wa Tamwil Islamic saving and loan cooperative institution have considerable potential in helping the community's economic development in the field of providing funds for the continuity of MSMEs in Karawang Regency. One of the efforts to develop BMT Rukun Abadi Islamic financial services in Karawang Regency requires studies to formulate the development strategy. This research uses descriptive qualitative analysis and Strengths, Weaknesses, Opportunities, and Threats (SWOT) analysis. The results of this study explain the strategies needed to overcome problems and to develop the BMT Rukun Abadi branch of Karawang Regency. These strategies include (1) product development strategy (2) location development strategy (3) HR development strategy (4) marketing development strategy. The strategy that has been prepared is intended to be able to increase competitiveness with other BMTs in the same region.